PLAY MATERIALS AND TEACHERS KNOWLEDGE OF GOALS OF PLAY IN PRE-PRIMARY SCHOOLS IN UYO URBAN, AKWA IBOM STATE - Ubong, Samuel Esu; Iniobong, Eyo Timothy (Journal of Early Childhood and Primary Education, 2020)
The research study investigated play materials and teachers’ knowledge of goals of play activities in pre-primary schools in Uyo Urban of Akwa Ibom State. Three research questions guided the study. The researchers adopted the survey design. The population of the study consisted of all the 685 teachers in all the 18 pre-primary schools in Uyo Urban. The sample of the study consisted of 60 teachers randomly drawn from the pre-primary schools in Uyo Urban of Akwa Ibom State. Frequency, percentage and rank order were used to analyze and interpret the data. The findings on the play materials showed pre-primary schools in Uyo Urban have materials for both the outdoor and indoor activities but their availability varies from school to school. The findings also revealed that teachers are knowledgeable about the role of play activities in children’s creative and cognitive development especially on the physical development. This seems to suggest that play activities are not mutually exclusive; hence children’s development should be considered holistically through play activities. The following recommendations among others were made, flexible outdoor play components needed by adding equipment and materials capitalizing on the natural features of the play space, creating interest area and active time block each day should be reserved for activities from which the children can select and suggestions for further research were made on the basis of the findings.